The Biomechanical Stability of Bone Staples in Cortical Fixation of Tendon Grafts for Medial Collateral Ligament Reconstruction Depends on the Implant Design. Issue 14 (December 2022) - Deichsel, Adrian; Raschke, Michael J.; Herbst, Elmar; Peez, Christian; Oeckenpöhler, Simon; Briese, Thorben; Wermers, Jens; Kittl, Christoph; Glasbrenner, Johannes
Background: The promising biomechanical stability of bone staples (BSs) in cortical fixation of tendon grafts for medial collateral ligament (MCL) reconstruction has been revealed by a previous investigation. However, it is currently unknown if the biomechanical stability of cortical fixation of tendon grafts depends on the BS design. Purpose: To assess the biomechanical stability of cortical fixation of tendon grafts in knee surgery using 4 different BS designs. Study Design: Controlled laboratory study. Methods: Cortical fixation of tendon grafts was performed in a porcine knee model at the tibial insertion area of the MCL using 4 different BS designs (n = 40): 8-mm width without spikes (n = 10), 8-mm width with spikes (n = 10), 14-mm width with spikes (n = 10), and 13 mm–wide 4-prong staples with spikes (n = 10). Specimens were mounted in a materials testing machine, and cyclic loading was applied to the tendon graft (500 cycles at 50 and 100 N, respectively), followed by load-to-failure testing. The Kruskal-Wallis test was performed for statistical analysis ( P < .05), and the post hoc Dunn test was performed for multiple comparisons. Results: In 4 of 10 specimens with graft fixation using BSs without spikes, slippage of the tendon underneath the BS led to failure of the construct during cyclic loading to 100 N. In the other groups, no fixation failure was observed during cyclic loading. Furthermore, graft fixation using BSs without spikes was found to have significantly more elongation during cyclic loading (8.2 ± 1.9 mm) and a lower ultimate failure load (170 ± 120 N) compared with graft fixation using narrow BSs with spikes (3.4 ± 1.2 mm [ P < .0001] and 364 ± 85 N [ P < .05], respectively) and graft fixation using broad BSs with spikes (4.5 ± 1.4 mm [ P < .05] and 429 ± 67 N [ P < .001], respectively). No statistical differences in elongation during cyclic loading or ultimate failure load were found between 4-prong staples with spikes (5.0 ± 1.3 mm and 304 ± 85 N) and narrow or broad staples with spikes. Conclusion: The biomechanical stability of cortical fixation of an MCL graft was comparable between each BS design with spikes (narrow, broad, and 4-prong) in a porcine knee model, whereas BSs without spikes led to failure of the fixation construct during cyclic loading in 4 of 10 specimens and increased elongation and lower ultimate failure loads in the remainder of the group. BSs without spikes may therefore not be recommended for graft fixation. Clinical Relevance: The use of BSs can help to avoid the conflict of converging tunnels in multiligament reconstruction surgery. An implant design with spikes yields significantly higher biomechanical stability than BSs without spikes.